A detailed record of the BELARE 2019－2020 meteorite recovery expedition on the Nansen Ice Field, East Antarctica - Steven Goderis; Mehmet Yesiltas; Hamed Pourkhorsandi; Naoki Shirai; Manu Poudelet; Martin Leitl; Akira Yamaguchi; Vinciane Debaille; Philippe Claeys (National Institute of Polar Research, 2021)
This report summarizes the Belgian Antarctic Expedition (BELARE) 2019－2020 meteorite search and recovery expedition near the Sør Rondane Mountains of East Antarctica during the 2019－2020 field season. This expedition took place from 15 January to 6 February 2020 within the area defined as ＂C＂ of the Nansen Ice Fields (S72°38'−72°48'S, 24°35'−25°06'E). The expedition team consisted of four scientists and two field guides, who systematically searched the ice field area and collected 66 meteorites. The total weight of the meteorites was determined to be ～8 kg. In addition to meteorites, blue ice samples, volcanic ash layers, and wind-blown terrestrial rock fragments were collected from the area to study in detail the nature of the mechanisms concentrating meteorites on the Nansen Ice Fields. The recovered meteorites were transported in a frozen state to the National Institute of Polar Research, Japan for dry-thawing and subsequent classification.